X-Linked Hypophosphatemic Rickets: Multisystemic Disorder in Children Requiring Multidisciplinary Management - Baroncelli, Giampiero Igli; Mora, Stefano (Frontiers in Endocrinology, 2021)
X-linked hypophosphatemic rickets (XLH) is the commonest inherited form of rickets. It is caused by an impaired regulation of fibroblast growth factor 23 (FGF23) due to a PHEX gene mutation, which leads to reduced tubular reabsorption of phosphate and renal 1-hydroxylase activity and increased renal 24-hydroxylase activity. Hypophosphatemia associated with renal phosphate wasting, normal serum levels of calcium, parathyroid hormone, and 25-hydroxyvitamin D represents the main biochemical sign in affected patients. Patients with XLH show rickets and osteomalacia, severe deformities of the lower limbs, bone and muscular pain, stunted growth, and reduced quality of life. However, XLH is a multisystemic disorder requiring multidisciplinary approaches in specialized subdisciplines. Severe complications may occur in patients with XLH including craniosynostosis, hearing loss, progressive bone deformities, dental and periodontal recurrent lesions, and psychosocial distress. Moreover, long-term conventional treatment with active vitamin D metabolites and oral inorganic phosphate salts may cause endocrinological complications such as secondary or tertiary hyperparathyroidism, and adverse events in kidney as hypercalciuria, nephrocalcinosis, and nephrolithiasis. However, conventional treatment does not improve phosphate metabolism and it shows poor and slow effects in improving rickets lesions and linear growth. Recently, some trials of treatment with recombinant human IgG1 monoclonal antibody that targets FGF23 (burosumab) showed significant improvement of serum phosphate concentration and renal tubular reabsorption of phosphate that were associated with a rapid healing of radiologic signs of rickets, reduced muscular and osteoarticular pain, and improved physical function, being more effective for the treatment of patients with XLH in comparison with conventional therapy. Therefore, a global management of patients with XLH is strongly recommended and patients should be seen regularly by a multidisciplinary team of experts.